Pengaruh Implementasi Kebijakan Standar Operasioal Prosedur Terhadap Kinerja Pegawai Pada Sekretariat Kota Manado - PURBA, IRA ELBERTNA; KIYAI, BURHANUDDIN; RUMAPEA, PATAR (JURNAL ADMINISTRASI PUBLIK, 2018)
This study starts from the problem that: the extent to which the implementation of a standard operating procedure policies on employee performance at Regional Secretariat Manado. Thus, this research aims: to analyze the effect of policy implementation of standard operating procedures on employee performance at Secretariat Manado. This study uses a quantitative approach to the application of descriptive and explanatory. information collected through questionnaires distributed to the technique 112 respondents, and is equipped with observation and documentation techniques, and then analyzed by applying the technique of frequency tables analysis, multiple linear regression and simple linear regression. Based on the analysis of data, it is known that: the distribution of respondents on all variables, both independent variables and the dependent variable / dependent as communication, resources and attitudes disposisi or executor implementation / application of the SOP, the average being "high" to be "moderate", while variables - bureaucratic structure variables and the implementation or application of SOP is still in the category of "moderate" tends to be high "high". Then the dependent variable or dependent (employee performance) is the category of "high" tend to be "moderate". Thus, it can be concluded that the implementation of a standard operating procedure policies its significant positive effect on employee performance and are jointly or simultaneously all the independent variables (communication, resources, dispositions / attitudes and bureaucratic structure) has a positive and significant impact on the implementation of SOP at Secretariat Manado City. Keywords: Implementation of policies, Standard Operational Procedures, employee performan